Inhibition of Colletotrichum gloeosporioides in yam crops at the Colombian Caribbean using essential oils of Curcuma longa and Zingiber officinale - Pérez Cordero, Alexander; Chamorro Anaya, Leonardo; Gomez, Jorge Mercado (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Essential oils are organic compounds during the last century have become important in the pharmaceutical sector because of its antimicrobial properties, being an alternative solution to certain plant diseases. In the present study, we evaluate in vitro the inhibitory activity of essential oils of Curcuma longa and Zingiber officinale against Colletotrichum sp. obtained from yam crops (Toluviejo, Sucre, Colombia). Concentrations 3,000; 5,000; 8,000 and 10,000 mg/L of each species of essential oils extractions were applied in vitro on the fungi (microwave assisted hydro-distillation method). In addition, we employed an absolute control, positive control (benomyl 1g/L) and a negative control. The inhibitory activity was performed by seeding the test surface and expressed as percentage of inhibition index. We obtain than the highest percentages of antifungal index were observed at 10000 mg/L, similar to that obtained with the positive control. Of the chemical characterization of essential oils (gas chromatography coupled with mass spectrometry) the secondary metabolite that occurred more range was the monoterpene 3-Thujeno and citral. The essential oils of C. longa and Z. officinale show inhibitory activity against the growth of Colletotrichum sp., and therefore can be employed to reduce the use of chemical compounds to reduce the anthracnose.